Clinical Symptoms and Outcomes of Severe Pneumonia Caused by Chlamydia psittaci in Southwest China - Yang, Fuxun; Li, Jiajia; Qi, Bo; Zou, Longfei; Shi, Zongming; Lei, Yu; Li, Jun; Luo, Xiaoxiu; Zeng, Fan; Lu, Sen; Huang, Xiaobo; Liu, Rongan; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Here, we aimed to retrospectively analyze the clinical characteristics of 27 patients with severe pneumonia caused by Chlamydia psittaci between January 2019 and April 2021 in southwest China. To this end, we collected data on the exposure history, clinical symptoms, laboratory examination, imaging characteristics, evolution, etiology, treatment, and outcomes to suggest a better diagnosis and prevention system. Our results showed that a metagenomic next-generation sequencing test could provide early diagnosis. All patients were sensitive to quinolones and tetracyclines, and the recovery rate was relatively high. Overall, all patients were in critical condition with moderate to severe acute respiratory distress syndrome and shock. In conclusion, early diagnosis of pneumonia caused by C. psittaci depends on effective molecular testing, and most patients recover after treatment.